Time-varying volatility in the U.S. labor market - Dennis Wesselbaum (Journal of Applied Economics, 2018)
In state-of-the-art macroeconomic and labor market models shocks are assumed to be homoscedastic. However, we show that this assumption is much too restrictive. We estimate the conditional variance-covariance matrix using a VAR-DCC model and discuss the time-varying risk contained in a large set of labor market variables. We find significant evidence for strong time-varying volatility in all considered labor market time series. We observe that recessions tend to lead peaks of volatility for most variables. Further, the effect of the Great Moderation does not hold for all variables. We also find different effects of supply-side and demand-side recessions. The implications are relevant for modelling purposes, forecasting, welfare analysis, and the understanding of sources of fluctuations.
Keywords: 330; Dynamic conditional correlation; multivariate GARCH; time-varying volatility; VAR-DCC